Transforming Microteaching Using Digital Islamic Picture Story Media - Eni Fariyatul Fahyuni; Ida Rindaningsih; Adi Bandono; Roslan Ab Rahman (Jurnal Pemberdayaan Masyarakat, 2025)
The transformation of microteaching using digital Islamic picture story media, “The Joy of Being Able to Give Alms” was proven effective in increasing student learning activity and instilling character education through stories about characters students know. This study uses a qualitative approach, conducted as a case study on microteaching activities for prospective elementary school teachers in Indonesia. The participants were selected using purposive sampling, which involved interviews, observations, and documentation. The implementation of this microteaching activity used subjects limited to eleven participants, including a) six elementary school students,  b) two students of the Faculty of Islamic Studies, University of Muhammadiyah Sidoarjo, c) three validators who were experts in the field of Islamic education and experts in innovative learning media. All data collected was limited to the opinions and experiences of participants. The activities showed that the pedagogical and professional teachers applied 1) meaningful learning, 2) educational interaction, 3) innovative and fun learning, 4) student-centered learning, and 5) instilling Islamic values. The use of digital Islamic picture story media has been proven effective in student learning and instilling character education through stories of characters that students are interested in.